PENGARUH KUALITAS PRODUK, CITRA MEREK, PERSEPSI HARGA DAN ELECTRONIC WORD OF MOUTH (EWOM) TERHADAP PROSES KEPUTUSAN PEMBELIAN (Studi Pada Konsumen Semarang Roru Cake) - Dewi Ayu Pratiwi, 15.05.51.0010; Tjahjaningsih, Endang (Students' Journal of Economic and Management, 2019)
This research goal to examine the effect of product quality, brand image, price perception and electronic word of mouth on the Semarang Roru Cake consumer purchasing decision process.The sampling method uses purposive sampling with certain considerations so that the samples used in this study were 97 respondents. The data used is primary data. The data is obtained directly from consumers Semarang Roru Cake who have made a purchase through a questionnaire method. The primary data was analyzed by SPSS through an instrument test in the form of validity and reliability tests, testing the research model in the form of coefficient of determination (R2) and F test, multiple linear regression and hypothesis testing in the form of t test.The results of this study indicate that partially, product quality variables have a positive and significant effect on the purchasing decision process, brand image variables have a positive and significant effect on the decision process, price perception variables have a positive and significant effect on the purchasing decision process and electronic word of mouth variables have a positive effect and significant to the process of purchasing decisions.